2013
DOI: 10.1162/pres_a_00145
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Agent Physicality and Social Presence for Medical Team Training

Abstract: Mixed reality and 3D user interface technologies have increased the immersion, presence, and physicality of user interactions. These technologies can also increase the physicality of embodied conversational agents (ECAs) by making the ECAs occupy and interact with the physical space. We propose that increasing the physicality of an ECA can increase the ECA's social presence, that is, the feeling that the ECA is a real person. In this paper, we examine existing research and formalize the idea of ECA physicality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Extant research indicates that the degree of perceived social presence in mediated communication can be enhanced with the aid of communication techniques and strategies, such as the use of avatars, emoticons, portrait pictures, and first name IDs (Bente, Ruggenberg, Kramer, & Eschenburg, 2008;Chuah et al, 2013;Reeves & Nass, 1996). Users of online forums typically have the option of using profiles to present themselves (Hinduja & Patchin, 2008;Liu, 2008).…”
Section: Social Presencementioning
confidence: 99%
“…Extant research indicates that the degree of perceived social presence in mediated communication can be enhanced with the aid of communication techniques and strategies, such as the use of avatars, emoticons, portrait pictures, and first name IDs (Bente, Ruggenberg, Kramer, & Eschenburg, 2008;Chuah et al, 2013;Reeves & Nass, 1996). Users of online forums typically have the option of using profiles to present themselves (Hinduja & Patchin, 2008;Liu, 2008).…”
Section: Social Presencementioning
confidence: 99%
“…Participants had a higher tendency to seek advice from the video or robotic human when making a choice with risk involved. In a medical training context, Chuah et al (2013) found that even partially increasing the physicality of virtual humans-here by adding a physical lower body (e.g., mannequin legs) to a display showing the virtual human's upper body-could increase the sense of social presence with the virtual human. In the aspect of tele-communication, Tanaka et al (2014) conducted an experiment using various communication media, including a virtual avatar and a robot, to check the effect of physicality on distant communication.…”
Section: Physicality and Gesturingmentioning
confidence: 99%
“…al. also presented interactive VHs in a medical application [7]. They developed the VHs with a physical body (e.g., mannequin legs) and concluded that increasing the physicality of VHs could increase social presence.…”
Section: Virtual Humans (Vhs)mentioning
confidence: 99%